Treatment with a sphingosine analog after the inception of house dust mite-induced airway inflammation alleviates key features of experimental asthma. Issue 1 (December 2015) - Gendron, David; Lemay, Anne-Marie; Tremblay, Claudine; Lai, Laetitia; Langlois, Anick; Bernatchez, Émilie; Flamand, Nicolas; Blanchet, Marie-Renée; Don, Anthony; Bossé, Ynuk; Bissonnette, Élyse; Marsolais, David
Abstract Background In vivo phosphorylation of sphingosine analogs with their ensuing binding and activation of their cell-surface sphingosine-1-phosphate receptors is regarded as the main immunomodulatory mechanism of this new class of drugs. Prophylactic treatment with sphingosine analogs interferes with experimental asthma by impeding the migration of dendritic cells to draining lymph nodes. However, whether these drugs can also alleviate allergic airway inflammation after its onset remains to be determined. Herein, we investigated to which extent and by which mechanisms the sphingosine analog AAL-R interferes with key features of asthma in a murine model during ongoing allergic inflammation induced byDermatophagoides pteronyssinus . Methods BALB/c mice were exposed to either D.pteronyssinus or saline, intranasally, once-daily for 10 consecutive days. Mice were treated intratracheally with either AAL-R, its pre-phosphorylated form AFD-R, or the vehicle before every allergen challenge over the last four days, i.e. after the onset of allergic airway inflammation. On day 11, airway responsiveness to methacholine was measured; inflammatory cells and cytokines were quantified in the airways; and the numbers and/or viability of T cells, B cells and dendritic cells were assessed in the lungs and draining lymph nodes. Results AAL-R decreased airway hyperresponsiveness induced byD. pteronyssinus by nearly 70%. This was associated with a strong reduction of IL-5 and IL-13 levels in the airways and with a decreased eosinophilic response. Notably, the lung CD4+ T cells were almost entirely eliminated by AAL-R, which concurred with enhanced apoptosis/necrosis in that cell population. This inhibition occurred in the absence of dendritic cell number modulation in draining lymph nodes. On the other hand, the pre-phosphorylated form AFD-R, which preferentially acts on cell-surface sphingosine-1-phosphate receptors, was relatively impotent at enhancing cell death, which led to a less efficient control of T cell and eosinophil responses in the lungs. Conclusion Airway delivery of the non-phosphorylated sphingosine analog, but not its pre-phosphorylated counterpart, is highly efficient at controlling the local T cell response after the onset of allergic airway inflammation. The mechanism appears to involve local induction of lymphocyte apoptosis/necrosis, while mildly affecting dendritic cell and T cell accumulation in draining lymph nodes.